Analisis Bekerja Dalam Tinjauan Ekonomi Islam dengan Pendekatan Hadis Tematik - Noni Afrianty; Aan Supian (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This study to analyze the hadith abput working thematics methods. This type of research is library research with a qualitative approach. The source of data in this study is five books through the hadissoft application. Analysis techniques using thematics methods through 11 (eleven) stages. The result of this research show that work is a command and test for all mankind and is of good value before Allah Almighty. Mankind gets and eats what his own hands strive, so everyone must have good work motivation and a high work ethic so that it will improve their abilities